Team Incentives, Social Cohesion, and Performance: A Natural Field Experiment - Josse Delfgaauw; Robert A. J. Dur; Okemena Abraham Onemu; Joeri Sol (Tinbergen Institute, 2019)
We conduct a field experiment in a Dutch retail chain with 122 stores to study the interaction between team incentives, team social cohesion, and team performance. Theory predicts that the effect of team incentives on team performance depends on a team's social cohesion. In particular, free-riding should be weaker when co-workers care more about each other. Conversely, team incentives may lead to more co-worker support or to higher peer pressure and thereby can affect the team's social cohesion. We introduce short-term team incentives in a randomly selected subset of stores and measure for all stores, both before and after the intervention, the team's sales performance, the team's social cohesion as well as co-worker support and peer pressure. The average treatment effect of the team incentive on sales is 1.5 percentage points, which does not differ significantly from zero. In line with theory, the estimated treatment effect strongly increases in social cohesion as measured before the intervention. We find that social cohesion itself is not affected by the team incentives. Our study illustrates the potential of complementing a field experiment with ex ante and ex post questionnaire data collection for the study of management practices, workplace behavior, and performance.
Keywords: C93; M52; 330; field experiment; team incentives; social cohesion